2021
DOI: 10.1002/prp2.875
|View full text |Cite
|
Sign up to set email alerts
|

Serious adverse drug reactions in sub‐Saharan Africa in the era of antiretroviral treatment: A systematic review

Abstract: The burden of adverse drug reactions (ADRs) in low-and middle-income countries (LMICs) may differ from that in high-income settings for a variety of reasons, including differences in disease burden, differences in drug utilization patterns, a potential lack of effective drug quality control, and the high risk for prescribing and dispensing errors that occur in overburdened healthcare systems. Previous systematic reviews summarizing the global burden of ADRs 1-6 included only a few surveys from LMICs, which lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…Systematic reviews of ADE occurrence in different settings are scarce in Africa, thereby making a comparison to earlier results difficult. A review by Moulton et al [ 10 ] reviewed the burden of serious ADRs in Sub-Saharan Africa and reported a median proportion of admissions attributed to ADRs was 4.8%, which was comparable to the finding from our study (6.0%). In addition, the prevalence of ADE-related hospital admissions aligned with data from international literature [ 96 , 97 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Systematic reviews of ADE occurrence in different settings are scarce in Africa, thereby making a comparison to earlier results difficult. A review by Moulton et al [ 10 ] reviewed the burden of serious ADRs in Sub-Saharan Africa and reported a median proportion of admissions attributed to ADRs was 4.8%, which was comparable to the finding from our study (6.0%). In addition, the prevalence of ADE-related hospital admissions aligned with data from international literature [ 96 , 97 ].…”
Section: Discussionsupporting
confidence: 89%
“…Two reviewers assessed the methodological quality of included observational studies using the ten-question criteria proposed by Smyth et al [ 15 ], considering that the widely used risk assessment approaches for systematic review such as Cochrane Risk of Bias tool and GRADE were primarily appropriate for randomized controlled trials. This ten-point quality assessment instrument employed in the current review was developed specifically for studies investigating ADEs in clinical settings and has been applied by previous systematic reviews [ 7 , 10 , 16 , 17 ]. We replaced the term severity with “seriousness or severity” in Smyth et al’s.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with the current findings, a systematic review by Mouton et al . [ 113 ] found a hospital mortality proportion of 2.5% to 16% among HIV-infected adults on HAART in SSA. According to a report from research conducted in seven teaching hospitals in Ethiopia, 22% of HIV-positive patients experience mild to life-threatening ARV drug toxicity [ 114 ].…”
Section: Discussionmentioning
confidence: 99%